Nurse Turnover Intentions: Do Support Systems and Self-Efficacy Affect Them? - Sinles Sitompul; Fery Agusman; Sonhaji Sonhaji (Jurnal Ners, 2026)
This study was conducted due to the large number of nurses who resigned in the 2024 period, which illustrates the low retention of nurses. The purpose of this study is to empirically prove the influence of support systems and self-efficacy on turnover intention. The research design used a cross sectional study, with a sample technique using purposive sampling which included 48 nurses in the inpatient unit as samples. The results of the analysis concluded that simultaneously and partially supervise and leadership style had an effect on the quality of nursing services. The implication of this study is the importance of education and training for room heads related to supervise techniques and also leadership management, according to the implications of the Neuman System which emphasizes the importance of considering all dimensions of human life holistically to provide comprehensive and meaningful nursing care.